Levodopa Dose-Limiting Dyskinesias in Treatment of Segawa Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the University of Cordoba, and other centers in Spain, Germany and New York report an atypical phenotype of persistent, low-dose levodopa treatment-limiting dyskinesias in 2 members of a family (female child aged 13 years and mother) with prominent brachial dystonia and a novel GCH1 mutation.